Changes in the sensitivity of GABAA current rundown to drug treatments in a model of temporal lobe epilepsy - Cifelli, Pierangelo; Palma, Eleonora; Roseti, Cristina; Verlengia, Gianluca; Simonato, Michele (Frontiers in Cellular Neuroscience, 2013)
The pharmacological treatment of mesial temporal lobe epilepsy (mTLE), the most common epileptic syndrome in adults, is still unsatisfactory, as one-third of the patients are or become refractory to antiepileptic agents. Refractoriness may depend upon drug-induced alterations, but the disease per se may also undergo a progressive evolution that affects the sensitivity to drugs. mTLE has been shown to be associated with a dysfunction of the inhibitory signaling mediated by GABAA receptors. In particular, the repetitive activation of GABAA receptors produces a use-dependent decrease (rundown) of the evoked currents (IGABA), which is markedly enhanced in the hippocampus and cortex of drug-resistant mTLE patients. This phenomenon has been also observed in the pilocarpine model, where the increased IGABA rundown is observed in the hippocampus at the time of the first spontaneous seizure, then extends to the cortex and remains constant in the chronic phase of the disease. Here, we examined the sensitivity of IGABA to pharmacological modulation. We focused on the antiepileptic agent levetiracetam (LEV) and on the neurotrophin brain-derived neurotrophic factor (BDNF), which were previously reported to attenuate mTLE-induced increased rundown in the chronic human tissue. In the pilocarpine model, BDNF displayed a paramount effect, decreasing rundown in the hippocampus at the time of the first seizure, as well as in the hippocampus and cortex in the chronic period. In contrast, LEV did not affect rundown in the hippocampus, but attenuated it in the cortex. Interestingly, this effect of LEV was also observed on the still unaltered rundown observed in the cortex at the time of the first spontaneous seizure. These data suggest that the sensitivity of GABAA receptors to pharmacological interventions undergoes changes during the natural history of mTLE, implicating that the site of seizure initiation and the timing of treatment may highly affect the therapeutic outcome.